Resilience and self-efficacy beliefs: A study of immigrant adolescents - Μόττη-Στεφανίδη Φρόσω; Παυλόπουλος Βασίλης; Τάκης Νίκος; Ντάλλα Μαρίνα; Παπαθανασίου Αθανασία Χρυσούλα; Masten, Ann S. (Psychology: the Journal of the Hellenic Psychological Society, 2020)
The abstract is available in the PDF